A Cross-Sectional Study of Myopia and Morning Melatonin Status in Northern Irish Adolescent Children - Jane M. Fulton; Sarah C. Flanagan; Julie J. Sittlington; Diego Cobice; Sara Dobbin; Sara J. McCullough; Gareth Orr; Patrick Richardson; Kathryn J. Saunders (Journal of Ophthalmology)
Purpose. Previous studies have demonstrated an association between melatonin status and both refractive error and axial length in young adult myopes. This study aimed to determine if this relationship extends to a younger adolescent cohort. Methods. Healthy children aged 12–15 years provided morning saliva samples before attending Ulster University (55°N) for cycloplegic autorefraction and axial length measures. Participants completed questionnaires describing recent sleep habits and physical activity. Salivary melatonin was quantified using high-performance liquid chromatography-tandem mass spectrometry. Data collection for all participants occurred over a 1-week period (April 2021). Results. Seventy participants aged 14.3 (95% CI: 14.2—14.5) years were categorised by spherical equivalent refraction [SER] (range: −5.38DS to +1.88DS) into two groups; myopic SER ≤ −0.50DS (n = 22) or nonmyopic −0.50DS < SER ≤ +2.00DS (n = 48). Median morning salivary melatonin levels were 4.52 pg/ml (95% CI: 2.60–6.02) and 4.89 pg/ml (95% CI: 3.18–5.66) for myopic and nonmyopic subjects, respectively, and did not differ significantly between refractive groups (P = 0.91). Melatonin levels were not significantly correlated with SER, axial length, sleep, or activity scores (Spearman’s rank, all P > 0.39). Higher levels of physical activity were associated with higher sleep quality (Spearman’s rank, ρ = −0.28, P = 0.02). Conclusion. The present study found no significant relationship between morning salivary melatonin levels and refractive error or axial length in young adolescents. This contrasts with outcomes from a previous study of adults with comparable methodology, season of data collection, and geographical location. Prospective studies are needed to understand the discrepancies between adult and childhood findings and evaluate whether melatonin levels in childhood are indicative of an increased risk for future onset of myopia and/or faster axial growth trajectories and myopia progression in established myopes. Future work should opt for a comprehensive dim-light melatonin onset protocol to determine circadian phase.